Resident cardiac macrophages mediate adaptive myocardial remodeling - Wong, Nicole R.; Mohan, Jay; Kopecky, Benjamin J.; Guo, Shuchi; Du, Lixia; Leid, Jamison; Feng, Guoshuai; Lokshina, Inessa; Dmytrenko, Oleksandr; Luehmann, Hannah; Bajpai, Geetika; Ewald, Laura; et al. (Immunity (Cambridge, Mass.), 2021)
Cardiac macrophages represent a heterogeneous cell population with distinct origins, dynamics, and functions. Recent studies have revealed that C-C Chemokine Receptor 2 positive (CCR2+) macrophages derived from infiltrating monocytes regulate myocardial inflammation and heart failure pathogenesis. Comparatively little is known about the functions of tissue resident (CCR2−) macrophages. Herein, we identified an essential role for CCR2− macrophages in the chronically failing heart. Depletion of CCR2− macrophages in mice with dilated cardiomyopathy accelerated mortality and impaired ventricular remodeling and coronary angiogenesis, adaptive changes necessary to maintain cardiac output in the setting of reduced cardiac contractility. Mechanistically, CCR2− macrophages interacted with neighboring cardiomyocytes via focal adhesion complexes and were activated in response to mechanical stretch through a transient receptor potential vanilloid 4 (TRPV4)-dependent pathway that controlled growth factor expression. These findings establish a role for tissue-resident macrophages in adaptive cardiac remodeling and implicate mechanical sensing in cardiac macrophage activation. [Display omitted] •The failing heart contains heterogeneous subsets of resident and recruited macrophages•Resident cardiac macrophages promote adaptation and survival of the failing heart•Resident cardiac macrophages interact with cardiomyocytes via focal adhesion complexes•Resident cardiac macrophages sense mechanical stretch through TRPV4 channels Resident cardiac macrophages are key regulators of heart development and homeostasis; however, the role of these cells during disease is presently unclear. Wong, Mohan, Kopecky, et al. reveal that resident cardiac macrophages orchestrate adaptive remodeling and survival of the failing heart by sensing mechanical stimuli through a TRPV4 dependent mechanism.